In vivo dosimetry for proton therapy: A Monte Carlo study of the Gadolinium spectral response throughout the course of treatment - Brás, Mariana; Freitas, Hugo; Gonçalves, Patrícia; Seco, Joao (Medical physics, 2025)
Background In proton radiotherapy, the steep dose deposition profile near the end of the proton's track, the Bragg peak, ensures a more conformed deposition of dose to the tumor region when compared with conventional radiotherapy while reducing the probability of normal tissue complications. However, uncertainties, as in the proton range, patient geometry, and positioning pose challenges to the precise and secure delivery of the treatment plan (TP). In vivo range determination and dose distribution are pivotal for mitigation of uncertainties, opening the possibility to reduce uncertainty margins and for adaptation of the TP. Purpose This study aims to explore the feasibility of utilizing gadolinium (Gd), a highly used contrast agent in MRI, as a surrogate for in vivo dosimetry during the course of scanning proton therapy, tracking the delivery of a TP and the impact of uncertainties intra- and inter-fraction in the course of treatment. Methods Monte Carlo simulations (Geant4 11.1.1) were performed, where a Gd-filled volume was placed within a water phantom and underwent treatment with a scanning proton TP delivering 4 Gy. The secondary photons emitted upon proton-Gd interaction were recorded and assessed for various tumor displacements. The spectral response of Gd to each pencil beam irradiation is therefore used as a surrogate for dose measurements during treatment. Results Results show that the deposited dose at the target volume can be tracked for each TP scanning point by correlating it with the recorded Gd signal. The analyzed Gd spectral line corresponded to the characteristic X-ray \textk_α\ line at 43 keV. Displacements from the planned geometry could be distinguished by observing changes in the Gd signal induced by each pencil beam. Moreover, the total 43 keV signal recorded subsequently to the full TP delivery reflected deviations from the planned integral dose to the target. Conclusions The study suggests that the spectral response of a Gd-based contrast agent can be used for in vivo dosimetry, providing insights into the TP delivery. The Gd 43 keV spectral line was correlated with the dose at the tumor, its volume, and its position. Other variables that can impact the method, such as the kinetic energy of the incident protons and Gd concentration in the target were also discussed.